Incidence of Toxoplasma Gondii and Relationship with Some Inflammatory Factors in Babylon Province - Widad Hashim Yahya Almuhana1 , Ahmed Khudhair Al-hamairy2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
The study included collecting (60)-blood samples from people who were attending the Children’s MaternityHospital in Babylon Province ,then the Latex test was used to diagnose Toxoplasmosis. The results of thestudy showed that the percentage of infection with toxoplasmosis in Babylon Province was(11.66%),theinfection (IgG) for females was (9.61) out of (52)-samples, and the injury (IgM) for females was (3.84) outof (52) samples, whereas the infection was for males in relation to:IgG (0%) out of (8 samples) for the total percentage of IgG-against is(8.3%)IgM (0%) out of (8 samples) and the total percentage of IgM- antibody is(3.3%).Upon detection of (CRP)-proteins, the study included collecting (60)blood samples for people who werereferred to the Children’s Maternity Hospital in Babylon Governorate, and then the(CRP)-test and itsrelationship to toxoplasmosis were used. The study results showed that the total percentage of active phaseproteins for people with toxoplasmosis in Babylon Province, it reached 50% ((the percentage was in femalesby(53.84%) while the percentage in males was 25%)). The current study showed that the percentage ofsensitivity of (IgG ,IgM)-antibodies is (8.3%, 3.33%) respectively while the percentage of specificity of(IgG) and (IgM)-opposites was (91.66% ,96.6%) respectively.Objectives of The Study: Because of the recent spread of toxoplasmosis infection and the increase inmiscarriage rates among pregnant women, the present study aimed to determine the infection of this parasitein Babylon Governorate between males and females alike, as well as to know the prevalence of toxoplasmosisand its relationship to the active phase proteins CRP